Is orthostatic hypotension and co-existing supine and seated hypertension associated with future falls in community-dwelling older adults? Results from The Irish Longitudinal Study on Ageing (TILDA) - Kenny, Rose (My University, 2021)
Orthostatic hypotension (OH) often co-exists with hypertension. As increasing age affects baroreflex sensitivity, it loses its ability to reduce blood pressure when lying down. Therefore, supine hypertension may be an important indicator of baroreflex function. This study examines (i) the association between OH and future falls in community-dwelling older adults and (ii) if these associations persist in those with co-existing OH and baseline hypertension, measured supine and seated. Data from 1500 community-dwelling adults aged ≥65 years from The Irish Longitudinal Study on Ageing (TILDA) were used. Continuous beat-to-beat blood pressure was measured using digital photoplethysmography during an active stand procedure with OH defined as a drop in systolic blood pressure (SBP) ≥20 mmHg and/or ≥10 mm Hg in diastolic blood pressure (DBP) within 3 minutes of standing. OH at 40 seconds (OH40) was used as a marker of impaired early stabilisation and OH sustained over the second minute (sustained OH) was used to indicate a more persistent deficit, similar to traditional OH definitions. Seated and supine hypertension were defined as SBP ≥140 mm Hg or DBP ≥90 mm Hg. Modified Poisson models were used to estimate relative risk of falls (recurrent, injurious, unexplained) and syncope occurring over four year follow-up. OH40 was independently associated with recurrent (RR = 1.30, 95% CI = 1.02,1.65), injurious (RR = 1.43, 95% CI = 1.13,1.79) and unexplained falls (RR = 1.55, 95% CI = 1.13,2.13). Sustained OH was associated with injurious (RR = 1.55, 95% CI = 1.18,2.05) and unexplained falls (RR = 1.63, 95% CI = 1.06,2.50). OH and co-existing hypertension was associated with all falls outcomes but effect sizes were consistently larger with seated versus supine hypertension. OH, particularly when co-existing with hypertension, was independently associated with increased risk of future falls. Stronger effect sizes were observed with seated versus supine hypertension. This supports previous findings and highlights the importance of assessing orthostatic blood pressure behaviour in older adults at risk of falls and with hypertension. Observed associations may reflect underlying comorbidities, reduced cerebral perfusion or presence of white matter hyperintensities.
PUBLISHED
Keywords: Ageing